2011
DOI: 10.1111/j.1537-2995.2011.03154.x
|View full text |Cite
|
Sign up to set email alerts
|

Transfusion medicine in American undergraduate medical education

Abstract: Transfusion medicine content in American undergraduate medical education is variable and the influence of the TMAA program on contemporary medical school curricula is questionable. Future efforts in this area should focus on standardizing and improving undergraduate medical education in transfusion medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
1
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 13 publications
5
72
1
3
Order By: Relevance
“…Perhaps as a consequence of these limited requirements, medical schools do not emphasize transfusion medicine education, making room for the more heavily tested topics. Karp and coworkers determined that 17% of medical schools provided no didactic lectures on transfusion medicine topics, and of those that do, only about 50% of them provided more than 1 or 2 hours of content. Also, more than 41% of students do not recall ever having a transfusion lecture, regardless of whether the student actually received one .…”
Section: The Knowledge Of Transfusion Medicine–related Principles Reqmentioning
confidence: 99%
“…Perhaps as a consequence of these limited requirements, medical schools do not emphasize transfusion medicine education, making room for the more heavily tested topics. Karp and coworkers determined that 17% of medical schools provided no didactic lectures on transfusion medicine topics, and of those that do, only about 50% of them provided more than 1 or 2 hours of content. Also, more than 41% of students do not recall ever having a transfusion lecture, regardless of whether the student actually received one .…”
Section: The Knowledge Of Transfusion Medicine–related Principles Reqmentioning
confidence: 99%
“…Studies have been conducted in countries such as the United States, United Kingdom, Tunisia, Canada and Iran to assess the degree of knowledge about transfusion medicine of newly graduated doctors; all studies reported lower than expected results 9, 10, 11, 12. In a poll conducted in 86 medical schools in the United States, most had less than three hours in the curricular grid dedicated to transfusion medicine 5 . This study aims to investigate the situation of the teaching of transfusion medicine in medical schools in Brazil, by analyzing curricular grids available on the internet and reviewing the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Blood transfusions are the most performed procedure in American hospitals 5 . In Brazil, according to the Hemovigilance Report of the Brazilian Government Health Department (Agência Nacional de Vigilância Sanitária – ANVISA) published in 2014, 3,127,957 transfusions were conducted during 2012 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Transfusion medicine (TM) knowledge varies widely among resident physicians, leading to inappropriate blood product utilisation and increasing both adverse event risks and cost. Fewer than 20% of medical schools offer formal TM education during the clinical years when medical students (MS) could learn fundamentals of this highly interdisciplinary field while seeing real patients . Thus, newly minted interns often learn TM principles piecemeal on the job.…”
Section: What Problem Was Addressed?mentioning
confidence: 99%